Scratching an Invisible Limb A Lacanian Reading of Sam Shepard’s Buried Child - Moghadam, Nima Behroozi (International Journal of Emerging Trends in Social Sciences, 2018)
Alienation and loss appear as a pivotal theme in the majority of Sam Shepard’s family plays. This study intends to give a Lacanian reading of Sam Shepard’s Buried Child. Drawing primarily on Lacan’s linguistic theory of psychoanalysis, as well as his definition of psychosis, this study shows how Tilden’s alienation in the play stems from the foreclosure of the paternal metaphor in the symbolic registry of the psyche which, consequently, causes a malfunction in the process of oedipalization by leaving a hole in the Other where the Name-of-the-Father, as the metaphor for the law against incest, should appear. As a result, the subject is regressed to the imaginary where he can play the role of the phallus for the mother, which is manifested in the backstory of Buried Child as an act of incest between Tilden and Halie. Further, the incompetence of the father in the play in establishing the law is argued as being a circular curse that goes from generation to another.